Fabrication and optical characterisation of InGaN/GaN nanorods - Dai, Xi; Wen, Xiaoming; Latzel, Michael; Heilmann, Martin; Appelt, Christian; Feng, Yu; Yang, Jianfeng; Chen, Weijian; Huang, Shujuan; Shrestha, Santosh; Christiansen, Silke; Conibeer, Gavin (Proceedings of SPIE - The International Society for Optical Engineering, 2015)
We report the fabrication of densely packed InGaN/GaN nanorods with high hexagonal periodicity. Nanosphere lithography and reactive ion etching were adopted to fabricate the nanorods from planar multiple quantum wells (MQWs). Compared to the planar MQWs, the nanorods exhibit significant luminescence enhancement. This is mostly attributed to the increased radiative recombination and light extraction efficiency. Both photoluminescence and Raman measurements confirmed in-plane strain relaxation in the MQWs after nanofabrication. A reduction in strain-induced quantum confined Stark effect in the nanorods increased radiative recombination. This work is most crucial to the understanding of optical properties with respect to the carrier transport and recombination in InGaN/GaN nanorods.
CRIS-Team Scopus Importer:2023-03-07
Keywords: cathodoluminescence; Langmuir-Blodgett approach; Nanorods; photoluminescence; Raman; reactive ion etching